A new genus of silken-fungus beetle (Coleoptera: Cryptophagidae) from the Spanish Cretaceous amber. (October 2017) - Peris, David; Lyubarsky, Georgy Yu.; Perkovsky, Evgeny E.
Abstract: The Cretaceous new species and genus Albocryptophagus cantabricus gen. et sp. n. is described based on a fossil specimen from the El Soplao amber deposit (Spain). The new genus is similar to the extant genera Cryptophagus and Micrambe, but differs from them in the transverse pedicel, anterior angles of pronotum, pronotal margin unmodified, pronotal pits absent. Albocryptophagus gen. n. is undoubtedly the most ancient representative for the subfamily Cryptophaginae described up today. Because the saproxylic habits in recent species of the family, a similar behavior is inferred for this new fossil. It is a new example that agrees with the idea that fossil beetles from Mesozoic ambers are characterized by a saproxylic lifestyle.